Branding the Role Of the District Baznas in Madura Through Online-Based Digitalization in Efforts of Community Economic Empowerment - Haryanto, Rudy; Suaidi (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2023)
The duties and functions of BAZNAS are regulated in RI Law Number 23 of 2011 concerning the management of zakat, namely planning, implementing, and controlling the collection of zakat in terms of distributing zakat and utilizing zakat including reporting and being accountable for the movement of zakat. To optimize the duties and functions of BAZNAS nationally, the Government issued a Decree of the Director General of Islamic Community Guidance No DJ. II / 568 / the Year 2004. Based on this decision, Baznas was born and formed for Pamekasan, Bangkalan, Sampang, and Sumenep Regencies on Madura Island. The strategy for procuring HR in the context of revitalizing Regency BAZNAS in Madura based on e-commerce/ digitization of zakat online is carried out following existing regulations, namely BAZNAS Regulation Number 1 of 2019 concerning procedures for appointing and dismissing Provincial BAZNAS and Regency/City BAZNAS leaders and circular letter from the Head of BAZNAS No. 3 of 2018 concerning the dissemination of the decision of the Chairman of BAZNAS number 24 of 2018 concerning guidelines for the management of amil zakat at Provincial BAZNAS and Regency/City BAZNAS. This strategy is not yet fully accommodating to online digitization-based services. The promotion strategy for revitalizing the Regency BAZNAS in Madura based on e-commerce/ online zakat digitalization is carried out directly and indirectly. In online digitization, promotions are carried out by uploading advertisements inviting people to make donations of zakat, infaq, and sadaqah at BAZNAS Regency in Madura through their website and Facebook. The potential application of e-commerce/ digitization of zakat online in the context of revitalizing BAZNAS districts in Madura is not yet representative in serving the collection of zakat, infaq, and sadaqah funds through digitalization online. Empowerment of the Community's economy through online digitization at the Regency BAZNAS in Madura has not yet been carried out because the digital application owned by BAZNAS Regency in Madura is not representative. After all, it is still done directly/manually.